A study on the perceptions of selected UP students On the role of classroom lecture chair design in contributing to their learning - Isturis, Ma. Cassandra A.; Mayo, Adelaida V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT This multiple case study sought to determine the perceptions of selected College students on the role of classroom lecture chair design in contributing to their learning. Using purposive sampling, a total of sixty undergraduate students, enrolled at the time of the study in the University of the Philippines, Diliman campus, were selected to participate in the survey and interviews. Four units in the same campus, namely College of Arts and Letters (CAL), Media Center in the College of Mass Communication (CMC), College of Engineering (CoE), and National Institute of Physics (NIP) were chosen as the sites from where the classroom lecture chairs used by the respondents are located. The study utilized triangulation or multi-method for the data gathering which includes photo documentation, ocular observation, survey, interview and gathering of measurements. Anchored on the Theory of Ergonomics (Wilson & Corlett, 1990) and the Onion Theory of Comfort (Rybczynski, 1986), the results of the study were analyzed. The findings infer that the students' perceived the important role of classroom lecture chair design in enhancing their learning experience in terms of its function in providing comfort, support, and accessibility during their class lectures. This study recommends that University administration must allot enough budget for procurement of ergonomically-designed classroom lecture chairs and other furniture to promote well-being and productivity among the students. Likewise, the study recommends that interior design students, faculty, professionals, and furniture designers should also consider ergonomics in specifying and making designs for classroom lecture chairs.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Chair design -- Philippines